Assessing Organisational Performance Within Entrepreneurial Orientation Research: Where Have We Been and Where Can We Go from Here?. (March 2017) - Gupta, Vishal K.; Wales, William J.
Firm performance is a crucial aspect of research within the entrepreneurial orientation (EO) literature. Yet, only limited attention has been devoted to examining the range of performance targets and considerations in the EO literature. As a result, tendencies and biases in how firm performance is captured in EO studies are not well understood. The present study analyses the treatment of firm performance in a 25-year sample of EO research. Our state-of-the-science analysis reveals a tendency to develop novel combinative measures of performance within the EO literature. Additionally, a limited understanding of operational performance effects is evidenced in the sample. Finally, we observe a crucial need to investigate more tightly defined performance consequences stemming from EO. Implications and directions for future research are discussed.